PERBEDAAN KEJADIAN ANEMIA PADA IBU HAMIL ANTARA YANG MENGALAMI EMESIS GRAVIDARUM DAN HIPEREMESIS GRAVIDARUM DI PMB WIDYA HUSADA KOTA MALANG - Kristiana, Agnis Sabat; Supriyanti, Eka; Sumiatun, Sumiatun (STIKes Maharani Malang, 2019)
Introduction:Pregnancy is a condition where a woman has a growing fetus in her body. Anemia in pregnancy is a condition of the mother with a hemoglobin level below 11 gr%. Pregnant women who experience anemia in 2013 had 37.1% and in 2018 there were 48.9% (Riskesdas, 2018). Method: The purpose of the study was to determine the differences in the incidence of anemia in pregnant women between those who experienced emesis gravidarum and hyperemesis gravidarum in PMB Widya Husada, Malang City. This research uses correlational analytic design with cross sectional approach. The population in this study were 31 pregnant women aged 0-28 weeks who experienced emesis gravidarum and hyperemesis gravidarum with a total sampling technique. The place of this research was conducted at BPS Widya Husada, Malang City. Data collection tool uses a checklist instrument to see the incidence of anemia, emesis gravidarum and hyperemesis gravidarum. Data analysis using Chi Square test. Result and Analysis: From the results of testing with Chi Square test obtained P> 0.05 then Ho accepted Ha rejected. There was no difference in the incidence of anemia in pregnant women between those who experienced emesis gravidarum and hyperemesis gravidarum at BPM Widya Husada, Malang City. Discussion: It is expected that pregnant women will increase their knowledge about nutritional status by carrying out prenatal checks on a regular basis to detect earlier risks